The good, the bad and the ugly of eyewitness identification practice in police officers – a self-report survey study - Huang, Ching-Yu (Psychology, crime & law, 2020)
Witness identification practice of the police plays a critical role in the criminal proceedings. The current study examines police officers’ knowledge regarding factors affecting witness memory as well as witness interview and identification practices in Taiwan, after relevant judicial reform had been implemented for more than a decade. A total of 499 police officers in Taiwan participated in the survey to report their knowledge and actual practice of eyewitness interview and identification. The findings revealed strengths as well as weaknesses in their current practice. More disconcertingly, most (87.8%) of them did not receive relevant training, and those who received training scored lower in both eyewitness knowledge and witness identification practice than those who received no training. These findings suggested that operations of eyewitness identification were not completely in line with recommended best practice outlined in recent Judicial Reform and that the current training need to be improved to increase its effectiveness.